Compatibility studies of polypropylene (PP)-sago starch (SS) blends using DMTA - Hamdan, S.; Hashim, D. M. A.; Ahmad, M.; Embong, S. (Springer, 2000)
Sago starch (SS) was melt-blended with polypropylene (PP) with the concentration of SS in the blends varied between 10% and 50% by weight. Characterization of the PP/SS blends was carried out to gain some information on the miscibility between PP and SS and to gain insight into how well these materials behave thermodynamically with regard to the variation of the storage modulus (E′) and the loss tangent (tanδ) with temperature. The E′ and tanδ remained unchanged for SS between 10% to 33% but increased as SS reached 50%. The blend containing 50%SS was superior compared to the other blends in the dynamic mechanical thermal analysis (DMTA). Through the use of a Differential Scanning Calorimeter (DSC), the melting endotherm of the miscible blends was found to increase constantly with the increasing SS content. The tensile properties of the blends decreased with SS content. Examination of the blends with a Scanning Electron Microscope (SEM) showed that the SS granules were well dispers ed in the PP matrix.